Five pillars of Islam in relation to physical health, spiritual health and nursing implications - Zaw, Cho Cho; ., Myat Min @ Mohd Omar (Center for Islamization, Kuantan, 2018)
This study aimed to examine five pillars of Islam and their relationship with physical and spiritual health. The five pillars of Islam are the foundation of Muslim life, considered mandatory by believers, and Muslims are required to observe them with utmost dedication. They are summarized as Shahadah, Salah, Zakat Saum, and Hajj. he first pillar of Islam, declaration of faith (Shahadah) includes the most important concept, which is the complete submission to the will of Allah (SWT) by obeying and believing in Him. Spirituality in general is defined as “religious belief or the spiritual quality of something”, “a search for the sacred”, “personal growth, or an encounter with one's own inner dimension”. The World Health Organization (WHO) mentions spiritual health as one of four dimensions to well-being; physical, mental, social, and spiritual”. Moreover, holistic nursing practice includes treating people as a whole and attending to a client’s physiological, psychological, and spiritual needs. Thus, this study intends to further explore the unitary aspect of Islam that infuse each of the pillars, and their effects on physical, spiritual well-being and nursing implications associated with it. Five pillars of Islam are discussed from the Quran, Alhadith, and Sunnah (the sayings and traditions of the Prophet) as baselines, and further additions from the knowledge of the Islamic scholars. And it is noted that our practices based on the five pillars of Islam have not only positive effects on physical but also spiritual health. This paper pointed out that while performing obligatory duties as stipulated by Islam, one could achieve spiritual enhancement as well as physical strength and well being.